Android-Based Physical Fitness Assessment Application for Student of Senior High School 1 Kudus - supriyadi, hery; Rustiadi, Tri; Soenyoto, Tommy (Journal of Physical Education and Sports, 2021)
The purpose of this study is producing an android application product which makes it easier for physical education teachers and students to measure physical fitness. The problems of the study are 1). What is the android-based physical fitness assessment application for students of Senior High School 1 Kudus’ model? 2). How effective is the android-based physical fitness assessment application for students of Senior High School 1 Kudus?The results of this study is an android-based application product of physical fitness test for students of Senior High School 1 Kudus which is effective and attractive to use by both physical education teachers and students. The validation result by material experts in all aspect is "Very Good" with an average score of 93.13%, the media experts’ assessment to product is "Very Good" with an average score of 89.09%, the teachers’ assessment to the product is "Very Good "with an average score of 85.38%, assessment by the large group students is" Very Good "with an average score of 85.11%. This study concludes that a product of android-based physical fitness assessment application has been produced and the teachers, students and parents can download it in the Play store by keyword "SIKESA". The implication of the research is that "SIKESA" can simplify the physical education learning process and become a learning resource which can be used by students to learn independently.